An analysis of electrical and optical characteristics of a type II superlattice for optical switching applications. (May 2015) - Rahman, M; Rouf, A S M S; Mohammedy, F M
Abstract: The present work demonstrates an analysis of electronic and optical characteristics of InAs/GaSbType II superlattice based photodetectors. The electronic characteristics are analyzed by developing a model of the Type II superlattice. The 8 band k.p method is implemented to deduce the wavefunctions. The effects of temperature on zero-bias resistance- area product (R0 A) are also included in the model. The newly proposed M-Structure design method is also implemented for our model. Electrical and optical properties of the material such as dark current density and absorption coefficient are calculated. At 50mV reverse bias, the dark current density is found equal to 1.5×10 -4 A/cm 2 . These calculations are done based on the approximation based models of reflectivity. These results were used to demonstrate the variation of optical properties with applied bias voltage to be used as a novel optical switching technique in WDM based communication networks.